2018
DOI: 10.1016/j.chb.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social cues in persuasive social robots on psychological reactance and compliance

Abstract: A B S T R A C TPeople can react negatively to persuasive attempts experiencing reactance, which gives rise to negative feelings and thoughts and may reduce compliance. This research examines social responses towards persuasive social agents. We present a laboratory experiment which assessed reactance and compliance to persuasive attempts delivered by an artificial (non-robotic) social agent, a social robot with minimal social cues (human-like face with speech output and blinking eyes), and a social robot with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…If the agent is a person, the attributes influencing the quality of interaction can be the length of the relationship (early encounters or later interactions), the character of the person, the aesthetics of the person (Dion et al, 1972), the degree of mutuality of his/her behavior. If the agent is a social robot, the characteristics influencing the quality of interaction can be the term of exposure to the interaction (i.e., short-term vs long-term), the social cues that the robot displays (Ghazali et al, 2017a and2018a), the language it uses (Ghazali et al, 2017a and2017b), its appearance (Wu et al, 2012;Wrobel et al, 2013;Ghazali et al, 2018b), the reciprocity of its behavior (Leite et al, 2014), and its contingent responsiveness (Díaz-Boladeras, 2017).…”
Section: Engagement With An Agentmentioning
confidence: 99%
“…If the agent is a person, the attributes influencing the quality of interaction can be the length of the relationship (early encounters or later interactions), the character of the person, the aesthetics of the person (Dion et al, 1972), the degree of mutuality of his/her behavior. If the agent is a social robot, the characteristics influencing the quality of interaction can be the term of exposure to the interaction (i.e., short-term vs long-term), the social cues that the robot displays (Ghazali et al, 2017a and2018a), the language it uses (Ghazali et al, 2017a and2017b), its appearance (Wu et al, 2012;Wrobel et al, 2013;Ghazali et al, 2018b), the reciprocity of its behavior (Leite et al, 2014), and its contingent responsiveness (Díaz-Boladeras, 2017).…”
Section: Engagement With An Agentmentioning
confidence: 99%
“…Earlier works [54][55][56] reported both positive and negative responses to social cues in robots. Perhaps counter-intuitively, the studies by Ghazali et al [14,25,57] suggested that persuasive robots were more effective when endowed with only minimal social cues such as eye-blinking rather than implementing several cues at once, e.g., combining head movement, eye expression and intonation in the voice. Further, it has been shown that persuasive robots should be designed with likable social features such as having a neutral face (less expressive) and facial characteristics that were known to evoke trust (see [58]).…”
Section: The Current Studymentioning
confidence: 99%
“…Using the social cues that were found to be positively perceived by humans in the earlier studies [14,25,57], this study mainly aims to extend the technology acceptance (TAM) to account for the influence of social responses onwards the persuasive robot. This study is developed to:…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were then asked to write down their thoughts after being persuaded by the robot and to label each thought as positive (P), neutral (Neu) or negative (N). Only negative cognitions were counted in calculating the psychological reactance score using the steps taken by Dillard and Shen (2005) [20] (see also [53]).…”
Section: Psychological Reactancementioning
confidence: 99%